Do non-wage cost rigidities slow down employment? Evidence from Turkey - Sinem H. Ayhan (IZA Journal of Labor Policy, 2013)
This paper examines the role of non-wage cost rigidities in slowing down employment creation by assessing the effect of a policy aimed at fostering employment for women and young men introduced in Turkey in 2008. Exploiting a difference-in-difference-in differences strategy, I assess the employment effect of the reduction in the employer contribution share of the social security premiums. The results, net of the recent crisis effect, suggest a positive effect of the reduction in non-wage costs on employment creation for the targeted group (women) shortly after the announcement of the policy.
Keywords: C31; J08; J21; J32; 330; Social security contribution cut; Employment creation; Policy evaluation